Customer Satisfaction towards Paragliding Services in Pokhara - Magar, Bikash Thapa; Lamichhane, Deennath; Adhikari, Surya Mohan; Chalise, Dibbya Laxmi; Chalise, Shilu (Janapriya Journal of Interdisciplinary Studies, 2019)
Customer satisfaction is an important aspect of successful business. So, every business should maintain a good relationship with its customers to enhance loyalty and increase profit. Many tourists participate in paragliding in Pokhara. Its revenue contribution is Rs. 300 million to Rs. 500 million per year. This research aims to assess the overall satisfaction of customers in paragliding through measurement of perceived service quality and perceived service value applying descriptive and analytical methods. The former is measured by the constructs: Reliability, Assurance, Tangibility, Empathy, and Responsiveness while the latter is measured by the constructs: Price, Scenery, and Thrill. The landing site near Phewa Lake was chosen as the study area. A convenient sample of 150respondents was selected for the study. Questionnaire was constructed to elicit primary data on independent variables and was evaluated on five-point Likert Scale. Focused group discussions supplemented the study. Mean score of different variables revealed that the contribution of perceived service quality to customer satisfaction is higher than that of perceived service value. Among the four significant variables- Reliability, Price, Scenery, and Thrill, the Reliability has higher contribution in Perceived Service Quality measurement. Similarly, the Price has higher contribution in Perceived Service Value Measurement. Overall, the level of satisfaction in paragliding among customers is found good. Further studies are needed to establish causal relationship between customer satisfaction and other demographic variables.